A novel multiple super junction power device structure with low specific on-resistance - 朱辉 李海鸥 李琦 黄远豪 徐晓宁 赵海亮 (Journal of semiconductors, 2014)
A novel multiple super junction （MS J） LDMOS power device is proposed to decrease Ron due to lateral and vertical interactions between the N-pillar and P-pillar. In the studied device： multiple layers of SJ are introduced oppositely under surface S J; when compared with 2D-depleting of the conventional super junction （CSJ）, a 3D- depleted effect is formed in the MSJ thanks to vertical electric field modulation; and, current distribution is improved by deep drain, which increases the drift doping concentration and results in a lower on-resistance. The high electric field around the drain region by substrate-assisted depleted effect is reduced due to the charge balance result from the electric field shielding effect of the bottom S J, which causes the uniform electric field in the drift region and the high breakdown voltage. The numerical simulation results indicate that the specific on-resistance of the MSJ device is reduced by 42% compared with that of CSJ device, while maintaining a high breakdown voltage; the cell pitch of the device is 12 μm.